Survey on IoT: Security Threats and Applications - Irfan Ahmad; Mohammad Saber Niazy; Riaz Ahmad Ziar; Sabawoon Khan (Journal of Robotics and Control (JRC), 2021)
the rapid growth of the internet of things (IoT) in the world in recent years is due to its wide range of usability, adaptability, and smartness. Most of the IoT applications are performing jobs an automatic manner without interactions of human or physical objects. It’s required that the current and upcoming devices will be smart, efficient and able to provide the services to the users to implement such a new technology with a secure manner. Thus the security issues are exploring day by day by the researchers. IoT devices are most portable and light in nature so it has several issues such as battery consumption, memory, and as these devices are working open range so the most important is security. In this survey paper, we have elaborated on the security attacks with reference to the different kinds of IoT layers. In the last, we have presented some of the applications of the IoT. This study will provide assistance to the researchers and manufacturers to evaluate and decrease the attacks range on IoT devices.